KONSEP BELAJAR MENURUT ISLAM - Marita Lailia Rahman (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2016)
This article is about learning concept in Islam. The explanation is also about learning concept depending on the Islamic intellectual. Islam explains in the Qur’an that learning is obligation by every people. Learning is not limited time, age and place. We can learn not only in formal education but also non formal education. Learning to the great people as our teacher or learning everything in our life. This article will explain about learning concept, the significance of learning, learning purpose, and learning activity in Islam. The knowledge that will be received from this article has the goal to enlarge our mind and motivation for learning by every people. Keywords: Learning Concept, Islam